Conselho Municipal de Habitação de Belo Horizonte e o poder sobre a deliberação das diretrizes, planos e programas da Política Municipal de Habitação - Maria Clara Maciel Silva Bois (2013)
In this paper, I analyze the housing policy implemented in Belo Horizonte in the past 20 years. Specifically, I investigate the Municipal Housing Council influence in such policies. I show that the council has gradually lost its influence in policy implementation and guidelinesover the last few years.